Light-dependent regulation of neurotransmitter release from rod photoreceptor ribbon synapses involves an interplay of Complexin 4 and Transducin with the SNARE complex - Lux, Uwe Thorsten; Meyer, Jutta; Jahn, Olaf; Davison, Adam; Babai, Norbert; Gießl, Andreas; Wartenberg, Anna; Sticht, Heinrich; Brose, Nils; Reim, Kerstin; Brandstätter, Johann Helmut (Frontiers in Molecular Neuroscience, 2024)
Adaptation of photoreceptor sensitivity to varying light intensities is a fundamental requirement for retinal function and vision. Adaptive mechanisms in signal transduction are well described, but little is known about the mechanisms that adapt the photoreceptor synapse to changing light intensities. The SNARE complex regulators Complexin 3 and Complexin 4 have been proposed to be involved in synaptic light adaptation by limiting synaptic vesicle recruitment and fusion. How this Complexin effect is exerted is unknown. Focusing on rod photoreceptors, we established Complexin 4 as the predominant Complexin in the light-dependent regulation of neurotransmitter release. The number of readily releasable synaptic vesicles is significantly smaller in light than in dark at wildtype compared to Complexin 4 deficient rod photoreceptor ribbon synapses. Electrophysiology indicates that Complexin 4 reduces or clamps Ca 2+ -dependent sustained synaptic vesicle release, thereby enhancing light signaling at the synapse. Complexin 4 deficiency increased synaptic vesicle release and desensitized light signaling. In a quantitative proteomic screen, we identified Transducin as an interactor of the Complexin 4-SNARE complex. Our results provide evidence for a presynaptic interplay of both Complexin 4 and Transducin with the SNARE complex, an interplay that may facilitate the adaptation of synaptic transmission to light at rod photoreceptor ribbon synapses.